2016
DOI: 10.1038/srep26345
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ and Tumor Necrosis Factor-α Polarize Bone Marrow Stromal Cells Uniformly to a Th1 Phenotype

Abstract: Activated T cells polarize mesenchymal stromal cells (MSCs) to a proinflammatory Th1 phenotype which likely has an important role in amplifying the immune response in the tumor microenvironment. We investigated the role of interferon gamma (IFN-γ) and tumor necrosis factor alpha (TNF-α), two factors produced by activated T cells, in MSC polarization. Gene expression and culture supernatant analysis showed that TNF-α and IFN-γ stimulated MSCs expressed distinct sets of proinflammatory factors. The combination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 27 publications
5
64
0
Order By: Relevance
“…Immunostimulatory cytokines produced by TGF‐β CAR‐T cells may also directly contribute to reducing tumor cell numbers, as TNF‐α and IFN‐γ have been associated with restricted tumor cell growth . Importantly, in the in vivo tumor microenvironment, which includes other cell types absent from our experiments, immunostimulatory cytokines may recruit additional anti‐tumor mechanisms such as the polarization of macrophages and stromal cells toward proinflammatory phenotypes . Therefore, the anti‐tumor contribution of TGF‐β CAR‐T cells may be further enhanced in the more complex in vivo milieu.…”
Section: Discussionmentioning
confidence: 64%
“…Immunostimulatory cytokines produced by TGF‐β CAR‐T cells may also directly contribute to reducing tumor cell numbers, as TNF‐α and IFN‐γ have been associated with restricted tumor cell growth . Importantly, in the in vivo tumor microenvironment, which includes other cell types absent from our experiments, immunostimulatory cytokines may recruit additional anti‐tumor mechanisms such as the polarization of macrophages and stromal cells toward proinflammatory phenotypes . Therefore, the anti‐tumor contribution of TGF‐β CAR‐T cells may be further enhanced in the more complex in vivo milieu.…”
Section: Discussionmentioning
confidence: 64%
“…This result indicated that MIC3 was an effective inducer of TNF-α. During acute infection with T. gondii , TNF-α acts synergistically with IFN-γ, resulting in the elimination of intracellular pathogens35. However, MIC3 did not induce any IFN-γ secretion compared with OVA in splenocytes (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 96%
“…ELISA assay results indicated that the levels of IFN-γ and TNF-α were significantly increased in MUC1-CRT-infected BMDCs when compared with MUC1-infected BMDCs. Previous results have indicated that IFN-γ and TNF-α are essential immune effectors released by activated immunocytes (32,33,47). Therefore, the supernatant concentration of IFN-γ and TNF-α may indirectly represent the active extent of the immune system in vivo.…”
Section: Discussionmentioning
confidence: 99%